Is socioeconomic status less predictive of achievement in East Asian countries? A systematic and meta-analytic review. (2019) - Kim, Sung won
Highlights: Overall weighted correlation of East Asian countries' SES-achievement moderately positive, similar to the United States. A critical review of the literature presents a more mixed picture. Narrative suggests weaker SES-achievement association in East Asia, strengthening over time. Variation among East Asian countries emphasized. Non-linear or negative SES-achievement associations in China ( n  = 3). Abstract: Previous meta-analyses found a positive association between socioeconomic status and achievement in the United States, but none have attempted to synthesize the effect size in East Asia despite the accumulating research documenting this relationship. This study revealed a moderately positive overall effect size between SES and achievement in East Asian countries, comparable to the results of prior U.S. meta-analytic studies. These numbers were higher than expected in a centralized, standardized, and differentiated East Asian education system. A critical review of our total sample of 77 studies revealed a mixed picture. While half omitted any discussion of differences, the SES-achievement relationship tended to be described as weaker in East Asia, but strengthening over time and becoming increasingly similar to that observed in Western industrialized liberal economies. Wealth and achievement displayed non-linear negative associations in China, raising the need to revisit social stratification processes and their interaction with education in East Asia.